Shorter oars are more effective - Nolte, V. W. (Journal of Applied Biomechanics, 2009)
The purpose of this investigation was to clarify the effects of blade design and oar length on performance in rowing. Biomechanical models and equations of motion were developed to identify the main forces that affect rowing performance. In addition, the mechanical connection between the propelling blade force and the force that the rower applies on the handle was established. On this basis it was found that the blade design and oar dimensions play a significant role on the rowing performance. While rowers have found empirically that larger and/or hydrodynamically more efficient blade shapes need to be rowed with shorter oars, this article explains this tendency from a biomechanical point of view. Based on the presented evidence, it can be concluded that shorter oars will allow rowers to improve the propelling forces without increasing the handle forces. These findings explain tendencies that started with the introduction of new blade shapes in 1991. A 2 x 2 factorial ANOVA was used to test the significance of the oar shortenings that occurred with the introduction of larger blade surfaces while international record times improved during all those years. Consequently, the findings of this investigation encourage coaches to further experiment with shorter oars and oar manufacturers to continue their blade development that would lead to even shorter oars, with the goal of continuous rowing performance improvements.